Relative speed of processing determines color-word contingency learning. - Forrin, Noah; Macleod, Colin (Memory & Cognition, 2017)
In three experiments, we tested a relative-speed-of-processing account of color-word contingency learning, a phenomenon in which color identification responses to high-contingency stimuli (words that appear most often in particular colors) are faster than those to low-contingency stimuli. Experiment 1 showed equally large contingency-learning effects whether responding was to the colors or to the words, likely due to slow responding to both dimensions because of the unfamiliar mapping required by the key press responses. For Experiment 2, participants switched to vocal responding, in which reading words is considerably faster than naming colors, and we obtained a contingency-learning effect only for color naming, the slower dimension. In Experiment 3, previewing the color information resulted in a reduced contingency-learning effect for color naming, but it enhanced the contingency-learning effect for word reading. These results are all consistent with contingency learning influencing performance only when the nominally irrelevant feature is faster to process than the relevant feature, and therefore are entirely in accord with a relative-speed-of-processing explanation.